Dakwah Melalui Platform Youtube Di Era Digital - Nazilatul Laili Sa’adah; Rusma Yulidawati (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
Da'wah is an activity that calls and invites people to the path of truth, the phenomenon of da'wah is currently developing so rapidly and dynamically with the presence of information technology and the internet, so that da'wah can be carried out in cyberspace. This study aims to describe how the phenomenon of da'wah occurs in cyberspace, especially on YouTube. It is important to do research to see how the influence of the experience of communication and information on the development of da'wah in cyberspace. Data collection techniques were carried out by reading and collecting related literature and theoretical references related to research problems from various sources such as journals, books, articles, and other data on the internet. The results show that da'wah through YouTube is an effective digital da'wah media because it can transform religious knowledge to the community, and it can collaborate with other media, and alternative media to disseminate audio content that both individuals and institutions can be accessed safely and comfortably.Keywords: Da'wah, Youtube, Communication and Information